Vitamin B-12 Supplement Exerts a Beneficial Effect on the Seminiferous Epithelium of Cimetidine-Treated Rats - Beltrame, Flavia L.; Caneguim, Breno H.; Miraglia, Sandra M.; Cerri, Paulo Sérgio [UNESP]; Cerri, Estela Sasso [UNESP] (Karger, 2011)
Treatment of gastric ulcer with cimetidine reduces acid secretion and interferes in the vitamin B-12 absorption. Regarding the harmful effect of cimetidine on the seminiferous tubules, the aim of the present study was to verify if prolonged treatment with cimetidine causes vitamin B-12 deficiency and whether the testicular damages are attenuated by vitamin B-12 supplementation. Adult male rats received, for 50 days, cimetidine (CMTG), cimetidine and vitamin B-12 (CMT/B(12)G), vitamin B-12 (B(12)G) and saline solution (CG). Vitamin B-12 and homocysteine plasma levels were evaluated and the testes were embedded in glycol methacrylate for the morphometric analyses of total, epithelial and luminal areas of the seminiferous tubules, number of Sertoli cells and frequencies of tubules according to stages and containing Sertoli and germ cells in the lumen. Terminal deoxynucleotidyl-transferase mediated dUTP nick end labeling (TUNEL) method and proliferating cell nuclear antigen (PCNA) immunohistochemistry were carried out. CMTG showed TUNEL-positive Sertoli cells and significant reductions in the epithelial and total tu-bular areas, number of Sertoli cells and frequency of tubules VII-VIII. In the CMT/B(12)G, the number of Sertoli cells and the epithelial and total tubular areas were similar to CG. The number of Sertoli cells (in B(12)G) and the frequency of tubules at stages VII-VIII (in B(12)G and CMT/B(12)G) increased significantly; PCNA-positive Sertoli cells were found in these groups. Although cimetidine was not able to induce vitamin B-12 deficiency, this drug causes tubular atrophy due to Sertoli cell damage and loss of germ cells. However, vitamin B-12 supplement is able to stimulate spermatogenesis and restore the number of Sertoli cells, softening the harmful effect of cimetidine on spermatogenesis. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Testis; Histamine antagonist; Vitamin B-12; Morphometry; Spermatogenesis